Antecedents and outcomes of restaurant employees' food safety intervention behaviors. (April 2021) - Harris, Kimberly; Taylor, Scott; DiPietro, Robin B.
Highlights: Managers and line-level employees are significantly different decision-makers with regard to food safety intervention. Managers perceive threats at a higher level than line-level employees, but are more passive at intervening than line-level employees. Line leave-employees perceive they are in more control over threats than management. Position, years of experience, and level of training are significant predictors the perception of threats and intervene behaviors. Employees with the perceived highest levels of control over food safety threats and thus intervene are line-level employees, not management. Abstract: Restaurants are likely culprits of having foodborne illness outbreaks, causes of which are often linked to employees failing to control food threats during the flow of food. Research indicates that many food risks posed by restaurants could be thwarted if employees would intervene as threats are noticed. For unknown reasons, employees are not always motivated to reduced or eliminate threats when observing poor food safety behaviors, regardless of position, education, or experience in the industry. This study applies the elaboration likelihood model of persuasion (ELM) and protection motivation (PMT) theories to investigate employee reactions to food safety threats. Of keen interest was to identify employees of differing positions in the restaurant and to study how they react to food safety threats to either intervene, passively dismiss, or simply leave the location of the incident.